Geographic Origin Tracing and Variety Authentication of Vietnamese Mangoes (Mangifera indica L.) Using ICP–MS and Statistical Analysis - Bui Quang Minh; Tran Ha Minh Duc; Le Van Nhan; Le Viet Anh; Nguyen Hoang Khanh; Nguyen Ngoc Tung; Hoang Minh Tao; Nguyen Tien Dat; Nguyen Quang Trung; Nguyen Bich Ngoc; Nguyen Van Khanh; Truong Ngoc Minh (Journal of Analytical Methods in Chemistry, 2025)
Food traceability, which involves verifying the history and location of a product throughout its production, processing, and distribution, is increasingly vital for consumers and the food industry. As a major exporter of mangoes and the 13th largest supplier to the US, Vietnam faces challenges from rising trade volumes, leading to more instances of low-quality and fraudulent products. This study investigates the traceability of Vietnamese mangoes (Mangifera indica L.), particularly the high-value Hoa Loc variety, using an integrated approach with principal component analysis (PCA) and inductively coupled plasma–mass spectrometry (ICP–MS). Mango samples from Tien Giang, Vinh Long, Dong Thap, and Can Tho provinces were analyzed for their elemental composition. PCA revealed significant regional differences, with key elements for distinguishing mango samples including magnesium (Mg), cesium (Cs), iron (Fe), silver (Ag), molybdenum (Mo), strontium (Sr), antimony (Sb), rubidium (Rb), zinc (Zn), and copper (Cu). Notably, Can Tho samples had the highest Mg concentration (575.52 ± 42.29 μg/g), while Tien Giang samples had the lowest (80.06 ± 10.24 μg/g). Significant regional variations were also observed in Fe, Co, and Zn. These findings demonstrate the efficacy of advanced analytical techniques in verifying traceability and ensuring mango product quality. The study underscores the importance of robust analytical methods in combating food fraud and maintaining consumer trust.